2015
DOI: 10.1017/s1047951114002522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of invasive and non-invasive pressure gradients in aortic arch obstruction

Abstract: Background Aortic arch obstruction can be evaluated by catheter peak-to-peak gradient or by Doppler peak instantaneous pressure gradient. Previous studies have shown moderate correlation in discrete coarctation, but few have assessed correlation in patients with more complex aortic reconstruction. Methods We carried out retrospective comparison of cardiac catheterisations and pre- and post-catheterisation echocardiograms in 60 patients with native/recurrent coarctation or aortic reconstruction. Aortic arch o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The Doppler peak instantaneous BPG across the narrowing is then estimated by the modified Bernoulli equation. However, invasive cardiac catheterization measuring the peak-to-peak gradient across the CoA represents the gold standard in the pediatric population(13, 14). Although Doppler-measured BPG tends to overestimate catheter-measured BPG in many cases, Doppler peak instantaneous BPG correlates reasonably well with catheter peak-to-peak BPG in patients with native or recurrent CoA that do not have collateral vessels or retrograde flow during diastole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Doppler peak instantaneous BPG across the narrowing is then estimated by the modified Bernoulli equation. However, invasive cardiac catheterization measuring the peak-to-peak gradient across the CoA represents the gold standard in the pediatric population(13, 14). Although Doppler-measured BPG tends to overestimate catheter-measured BPG in many cases, Doppler peak instantaneous BPG correlates reasonably well with catheter peak-to-peak BPG in patients with native or recurrent CoA that do not have collateral vessels or retrograde flow during diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Peak instantaneous BPG was estimated using the modified Bernoulli equation (4×V 2 ). Peak instantaneous BPG values by ultrasound were only used in the current study to determine when absorption of the dissolvable Vicryl sutures used in creating CoA for the Corrected group of rabbits had occurred, since BPG by catheterization obtained as discussed below represents the gold standard and preferred method, when available(13, 14). Weekly ultrasound imaging revealed that the BPG remains elevated in Corrected rabbits for 34±2 days after surgical induction of the coarctation (range 32–37 days; Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Peak instantaneous gradient by echocardiogram is used commonly in clinical practice. However, multiple studies have highlighted its poor correlation with peak‐to‐peak gradient at catheterization …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Several studies have investigated the correlation between MRI measurements and echocardiography with catheterization for the estimation of the pressure drop in pulmonary circulation. The results have been inconsistent.…”
mentioning
confidence: 99%